The Effect Of Futsal On Improving The Physical Fitness Of Male Students In Class XI At Ma An-Nur Pagar Jati - Hamidi Ardiansyah; Asnawati Asnawati; Defri Anggara (Journal of Physical Education and Sports, 2026)
This study aims to determine the effect of Futsal Games on Improving Physical Fitness of Grade IX Male Students of MA An-Nur Pagar Jati. This type of research is experimental research. The research method used is a treatment by level design where the independent variable (X) is the futsal game training method. While the dependent variable (Y) is physical fitness. The number of samples is 17 students. The results of the study are that there is an Effect of Futsal Games on Improving Physical Fitness of Grade IX Male Students of MA An-Nur Pagar Jati which can be accepted as true. From the Pre-Test data, the average value is 11.00, then at the time of the Post-Test the average value reaches 15.41. The change in the average value of Physical Fitness can be seen from the difference in the average value of 4.41 from before being given futsal game treatment and after being given treatment. In addition to the increase in the average value of the final test (Post-Test), it is also seen in the analysis of data description, where in the pre-test there were no samples that obtained Physical Fitness values ​​in the very good and good classification, which were obtained by 3 people (18%) with a very poor classification, as many as 13 people (76%) with a poor classification, as many as 1 person (6%) with a moderate classification. While in the final test (Post-Test) there were values, where there were no very poor classifications, in the poor category obtained by 7 people (41%), as many as 5 people (29%) with a moderate classification, as many as 4 people (24%) with a Good classification and 1 person (6%) who achieved a very good classification. From the results of the explanation above, it can be concluded that futsal games have a significant influence on Physical Fitness. The futsal game is carried out with a lose-replace system with a time of 10 minutes, if 2 goals occur before 10 minutes then the losing team will be replaced before the time reaches 10 minutes continuously, and interspersed with an active break for 10 minutes before continuing to the second meeting.